Plan Estratégico para la Asociación de Pequeños Mineros Cuencas del Río Nambija y Quebrada de Cambana ubicada en la Parroquia San Carlos de las Minas perteneciente a la Provincia Zamora Chinchipe - Gonzalez Paredes, Susana Francisca (2016)
The implementation of a strategic plan has become very important in companies due to the great need to improve the development of the activities in which managers enter to achieve success. On the other hand, the insecurity generated by the accelerated changes in economic, social, political, technological and environmental factors and the lack of knowledge of their internal forces; Make managers prefer the implementation of the strategic plan. This thesis work is called "STRATEGIC PLAN FOR THE ASSOCIATION OF SMALL MINISTERS OF THE NAMBIJA RIVER AND CHANGE OF CAMBANA", whose main objective is to propose a strategic plan and specific objectives: to develop an external, sectoral analysis and the internal analysis in the company. The methodology applied in the research for the elaboration of the plan was formulated based on the collection of information of the personnel, on factors and external variables, an exploration about the competence and the analysis was realized to the functional areas. Techniques such as interview, surveys and observation guide were applied to the manager, workers and clients. The main results of the study were: The external analysis studying the political, economic, social, technological and ecological factors determining the opportunities and threats for the elaboration of the matrix of evaluation of external factors. Competitive analysis using the 5 forces of PORTER resulted in the matrix of the competitive profile. In the internal analysis, the internal factors evaluation matrix was developed, performing the respective analysis to the functional areas. In order to formulate the strengths, opportunities, weaknesses and threats, to design the SWOT matrix where it analyzes, observes and describes how the strengths and weaknesses interact with the threats and opportunities. The internal and external matrix was made according to the results obtained from the EFE matrix and the EFI matrix; Among the strategic objectives we propose are: "to develop the business philosophy, thus improving the efficiency and effectiveness of the personnel working in the association of small miners (mission, vision and values)"; "Elaborate the organizational structure that represents its different departments and lines of authority and a manual of functions for each one of the existing positions in the association to improve the administrative and operational part"; "To design a plan of training and motivation for the personnel of the association of small miners and thus to improve their work performance"; And "adapt the physical area and acquire computer equipment with high quality software for the accounting department that contributes to control and reflect in a timely manner financial statements." The total budget for the implementation of these objectives is $ 7.174,70, the value of which will be fully financed by the company. Finally, we present the conclusions and recommendations that are the result of our study, which will serve as a great contribution to the company in putting it into practice.